2016
DOI: 10.1371/journal.pcbi.1004968
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of Heart Failure Using a Rabbit Model: From the Failing Myocyte to Ventricular Fibrillation

Abstract: Heart failure is a leading cause of death, yet its underlying electrophysiological (EP) mechanisms are not well understood. In this study, we use a multiscale approach to analyze a model of heart failure and connect its results to features of the electrocardiogram (ECG). The heart failure model is derived by modifying a previously validated electrophysiology model for a healthy rabbit heart. Specifically, in accordance with the heart failure literature, we modified the cell EP by changing both membrane current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…The researchers concluded that the cardiac lesions developed in rabbit hearts after single dose x-ray exposure resembled the lesions seen in humans [40]. Rabbits have since only been used by a few researchers to study RIHD [41,[114][115][116][117][118], although this species is commonly used to study cardiovascular disease from other causes [119][120][121][122][123][124][125]. There might be unique benefits to studying electrophysiological changes caused by radiation in rabbit models over rat models, as the rabbits' Ca2+ transport, action potential duration, and main ionic currents underlying repolarization are similar to humans [113,126,127].…”
Section: Animal Species Used In Preclinical Studies Of Rihdmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that the cardiac lesions developed in rabbit hearts after single dose x-ray exposure resembled the lesions seen in humans [40]. Rabbits have since only been used by a few researchers to study RIHD [41,[114][115][116][117][118], although this species is commonly used to study cardiovascular disease from other causes [119][120][121][122][123][124][125]. There might be unique benefits to studying electrophysiological changes caused by radiation in rabbit models over rat models, as the rabbits' Ca2+ transport, action potential duration, and main ionic currents underlying repolarization are similar to humans [113,126,127].…”
Section: Animal Species Used In Preclinical Studies Of Rihdmentioning
confidence: 99%
“…Even among the larger animals, different species offer differing benefits. For example, models need to be selected carefully to address radiation-induced coronary alterations, an important component of human RIHD that needs additional study [6,[122][123][124][125][126][127]. The coronary circulation of pigs is similar to young human hearts (e.g., no anastomoses between branches of the vasculature), while the coronary circulation in dogs is more similar to older human hearts with ischemic heart disease (highly collateralized circulation) [129][130][131].…”
Section: Non-humanmentioning
confidence: 99%
“…Computational modeling of cardiac electromechanics (Krishnamoorthi et al, 2014 ) can provide mechanistic insight to normal and abnormal cardiac function and electrical wave propagation (Ponnaluri et al, 2016 ). Chronic myocardial infarction remains a substantial risk factor for both mechanical heart failure and fatal electric rhythm abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…We note here that this study considered an idealized and smooth geometrical representation of the ventricles of the human heart, useful for numerical verification purposes. It is important to note that such idealized domain does not include important anatomical structures such as the intricate endocardial surface, papillary muscles, and Purkinje network, that are currently included in advanced heart models (Ponnaluri et al, 2016 ; Sahli Costabal et al, 2016 ). Future work should focus in understanding how non-conforming formulations can handle such fine-scale anatomical details and structures.…”
Section: Discussionmentioning
confidence: 99%